The function of Ana1 in centrosome assembly, and the regulation of centriole growth in Drosophila - Saurya, S (2018)
Centrioles are microtubule-based structures that play a crucial role in the formation of centrosomes, cilia and flagella. Centriole defects are linked to several human diseases such as microcephaly, primordial dwarfism, cancer and ciliopathies. In Drosophila, Plk4, Sas-6, Ana2, Sas-4 and Asl form a conserved pathway that is essential for centriole assembly. Ana1 was identified as a potential centriole assembly protein in two genome-wide RNAi screens in Drosophila S2 cells, and ana1 mutant flies are uncoordinated, and their sperm are immotile. Thus, Ana1 appeared to have an important role in centriole assembly, but it was unclear how it functioned in the context of the known assembly pathway. The primary aim of my thesis was to characterise the function of fly Ana1 in vivo. I found that Ana1 is not essential for centriole assembly, but it helps recruit Asl to new-born centrioles to allow them to mature properly so that they can duplicate and organize mitotic PCM. Unexpectedly, I discovered that Ana1 also promotes centriole elongation in a dose-dependent manner. Several centriolar proteins can influence centriole length, but how they do so is unclear. In collaboration with several colleagues in the laboratory, we developed techniques that allowed us, for the first time, to monitor the kinetics of daughter centriole growth in Drosophila embryos. We found that Plk4 sets the size of the centriole cartwheel by enforcing an inverse relationship between the cartwheel growth rate and period. I found that Ana1 does not influence cartwheel growth, but I identified several other proteins that do so, most notably CP110 and Cep97, that normally bind to the distal end of the centrioles. These studies have provided several important new insights into how centriole length is regulated.